Dairy Products: Processing Technology and Sensory Properties (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
In recent decades, consumers’ preferences, habits, and expectations regarding food have changed, leading to a new landscape in which food is expected to be produced with natural ingredients, balanced chemical compositions, enhanced properties for promoting health, a long shelf-life, safety, and sustainable processing methods. In this context, the dairy sector is facing significant challenges in providing suitable products without impairing their sensory characteristics. This Special Issue presents 11 papers studying different research topics that address these needs, showcasing authors that focus on improving cheese shelf-life or preservation conditions, have developed innovative products with enhanced nutritional properties, and focus on the impact of processing on product quality and safety.